Perjanjian Kerja Waktu Tertentu (PKWT) Berdasarkan UU No 6/2023 Tentang Cipta Kerja Dan Hukum Islam - Deni Iskandar; Nurul Amalia; Muhammad Misbakul Munir (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research explores the Specific Time Work Agreement (PKWT) between workers and PT. Astra Autoparts. Using qualitative methods and a normative juridical approach, this research not only refers to regulations and related literature, but also involves observations and interviews with HRD and contract workers at the company. From an Islamic legal perspective, research emphasizes that PKWT must fulfill the principles of justice, equality and protection of workers' rights. The concept of "fair" (‘adl) is in focus, where respect for workers' rights and prevention of exploitation are key. It is hoped that the PKWT is in accordance with Law No. 6/2023 to create a fair work environment. The research results show that PT. Astra Otoparts has implemented PKWT in accordance with Government Regulation Number 35 of 2021 and Law no. 6/2023 concerning Job Creation. However, there are obstacles such as incompatibility of worker qualifications, lack of understanding of work contracts, lack of understanding of labor laws, and lack of understanding of government regulations regarding PKWT. Therefore, efforts are needed to increase understanding and conformity in the implementation of PKWT in order to create a fairer work environment.